Experiences of Women with Infertility attending Gynae OPD of Tertiary Hospital of Rupandehi - Gurung, Saraj; Ghimire, Sulochana; Kachapati, Anuja (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: One of the most important and underappreciated reproductive health problems in developing countries is the high rate of infertility and childlessness. The inability to have a child is frequently considered a personal tragedy affecting the entire family and even the local community.MATERIAL AND METHODS: The descriptive phenomenological research design was used to explore experiences of women with infertility. Fifteen women with infertility were selected by purposive sampling technique. Data was collected through in-depth interview method using unstructured questionnaire and thematic analysis was done.RESULTS: Among 15, 46.66% of the participants had gynecological problems and 53.33% had medical problems such as hypothyroidism and hyperthyroidism. Thirty-three percentage of participants' spouse had problem of low sperm count and absence of sperm. Most of the participants and their spouses were under treatment. Sixty percentage of the participants had experienced psychosocial problems and 26.66% had experienced physical and sexual problems because of infertility.CONCLUSION:  It is concluded that participants are suffered mainly from psychosocial problems beside that physical and sexual problems. Cent percent of the participants were under treatment and majority of participants said they will try for conception until fertility seized. One third of participants spouse had problem of sperm. It is recommended to concerned authority of hospital to provide couple counseling regarding infertility